Transformação dos sistemas técnicos da agricultura familiar camponesa em Cametá, Pará: a intervenção da Associação Paraense de Apoio as Comunidades Carentes (APACC) - SCALABRIN, Andreia Cristine (Universidade Federal do Pará, 2021)
This paper evaluates the results of APACC'sperformance in the changes made in the productive systems of lowland and upland, with the encouragement and support that this NGO provides agriculturists with the aim of increasing productivity of farms throughout sustainable practices. It is made from the comparison of production of